Characterization of neurobehavioral pattern in a zebrafish 1-methyl-4-phenyl-1,2,3,6- tetrahydropyridine (MPTP)-induced model: a 96-hour behavioral study - RazaliI, Khairiah; Mohd Nasir, Mohd Hamzah; Othman, Noratikah; Doolaanea, Abd Almonem; Kumar, Jaya; Ibrahim, Wisam Nabeel; Mohamed, Wael Mohamed Yousef (Public Library of Science, 2022)
Parkinson’s disease (PD) is the most common brain motor disorder, characterized by a substantial loss of dopaminergic neurons in the substantia nigra pars compacta (SNpc). Motor impairments, such as dyskinesia, bradykinesia, and resting tremors, are the hallmarks of PD. Despite ongoing research, the exact PD pathogenesis remains elusive due to the disease intricacy and difficulty in conducting human studies. Zebrafish (Danio rerio) has emerged as an ideal model for researching PD pathophysiology. Even though 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) has been used to induce PD in zebrafish, behavioural findings are frequently limited to a single time point (24 hours post-injection). In this sense, we aim to demonstrate the effects of MPTP on zebrafish swimming behaviour at multiple time points. We administered a single dosage of MPTP (200μg/g bw) via intraperitoneal injection (i/p) and assessed the locomotor activity and swimming pattern at 0h, 24h, and 96h post-injection through an open field test. Analysis of the behaviour revealed significant reductions in swimming velocity (cm/s) and distance travelled (cm), concurrent with an increase in freezing maintenance (duration and bouts) in zebrafish injected with MPTP. In addition, the MPTP-injected zebrafish exhibited complex swimming patterns, as measured by the turn angle, meander, and angular velocity, and showed abnormal swimming phenotypes, including freezing, looping, and erratic movement. To conclude, MPTP administration into adult zebrafish induced hypolocomotion and elicited motor incoordination. Plus, the effects of MPTP were observable 24 hours after the injection and still detectable 96 hours later. These findings contribute to the understanding of MPTP effects on adult zebrafish, particularly in terms of swimming behaviours, and may pave the way for a better understanding of the establishment of PD animal models in the future.